Correlation Of Care Compliance With Controlled Blood Pressure In Hypertension Patients - Ni Komang Winda Dwi Latri; Awan Dramawan; Sugijati Sugijati (Universitas STRADA Indonesia, 2021)
Hypertension is a condition in which there is an abnormal and continuous increase in blood pressure on several blood pressure checks caused by one or more risk factors that do not work properly in maintaining normal blood pressure. This research design uses non-experimental with the form of a correlational research design that examines the relationship between variables. Data were collected using a questionnaire. Data analysis using the Spearman Rank statistical test. The sampling technique used was purposive sampling that the sample obtained was 94 respondents.The results showed that respondents who were adherent to hypertension treatment had controlled blood pressure values. The statistical test with the Spearman Rank with shows that = 0,000, meaning that there is a relationship between treatment adherence and controlled blood pressure in hypertensive patients. This study is that there is a relationship between treatment adherence and controlled blood pressure in hypertensive patients at Meninting Health Center.